Akuntabilitas Kinerja Pegawai Badan Pengelolaan Keuangan dan Asset Kabupaten Pamekasan - Husein, Mohammad Bustanol; Ma'mun, Sukron (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
The implementation of good governance requires the government to improve its bureaucratic system so that a more accountable government is formed so that the government becomes more efficient, effective, clean and responsible and free from a culture of corruption, collusion and nepotism. The Pamekasan Regency Financial and Asset Management Agency as a government agency authorized to manage Pamekasan Regency finances and assets is obliged to be responsible for its performance in achieving the vision and mission that has been formulated. The purpose of this study was to determine the accountability of employee performance at the Pamekasan Regency's Financial and Asset Management Agency. This research uses descriptive qualitative research, because it seeks to explain the reality of accountability in the performance of employees of the Pamekasan Regency's Financial and Asset Management Agency. Data collection uses in-depth interview techniques and documentation. Data analysis in this study uses the Text and Language Analysis Method, namely Content Analysis. The results showed that, performance accountability carried out by individual employees was still not going well because in the application of the five dimensions of performance accountability namely legal accountability and honesty, managerial accountability, program accountability, policy accountability and financial accountability were not in line with expectations. In this case, the improvement of the lack of performance accountability carried out by individual employees must be by means of instilling control (self) in each individual employee to be successful in taking responsibility for their performance. Results Performance achievements carried out by individual employees are evaluated for the accountability of their performance and are required to account for their performance in carrying out what are the main tasks, functions and responsibilities mandated to employees.